Isolation and Identification of Profenofos Pesticide-Tolerant Bacteria from Agriculture Land in Sleman Regency - Pertiwi, Melania Citra; Rakhmawati, Anna; Octavia, Bernadetta; Aminatun, Tien; Suhartini (Jurnal Sains Dasar, 2025)
The intensive application of organophosphate pesticides containing profenofos as the active compound may lead to soil contamination and the emergence of pesticide-tolerant bacterial strains with potential for bioremediation. Comprehensive identification and characterization of these bacteria are crucial to support sustainable agricultural and environmental management practices. The aim of the study is to analyze the characteristics and identify indigenous bacteria tolerant to profenofos pesticide in Sleman agricultural land, DIY. This study is qualitative research using an exploratory-descriptive. Isolation was carried out by dilution to a level of 10-7 followed by a spread plate on Mineral Salt Medium (MSM) which was given with 100 ppm profenofos pesticide. Bacterial isolates were characterized and then identified using profile matching with reference genera. Based on the results of the study, it is found that 10 bacterial isolates tolerant to organophosphate pesticide with the active ingredient profenofos that have a similarity index of ≥70%. Based on the reference bacteria, 5 different genera are obtained, namely Paracoccus (D3, D8), Micrococcus (D5, D6, D9), Enterococcus (D2, D10), Arthrobacter (D1, D4), and Neisseria (D7). The bacterial isolates obtained have different characteristics. The characteristics of these bacteria are gram positive and negative bacteria with round, irregular, and rhizoid shapes. Their margins are lobate, curled, entire, undulate, and ciliate. Their elevations are umbonate, raised, and flat. The color of the bacteria is white to light orange, with various physiological test results.